Diverse roles of Tup1p and Cyc8p transcription regulators in the development of distinct types of yeast populations - Váchová, Libuše; Palková, Zdena (Current genetics, 2019)
Yeasts create multicellular structures of varying complexity, such as more complex colonies and biofilms and less complex flocs, each of which develops via different mechanisms. Colony biofilms originate from one or more cells that, through growth and division, develop a complicated three-dimensional structure consisting of aerial parts, agar-embedded invasive parts and a central cavity, filled with extracellular matrix. In contrast, flocs arise relatively quickly by aggregation of planktonic cells growing in liquid cultures after they reach the appropriate growth phase and/or exhaust nutrients such as glucose. Creation of both types of structures is dependent on the presence of flocculins: Flo11p in the former case and Flo1p in the latter. We recently showed that formation of both types of structures by wild Saccharomyces cerevisiae strain BR-F is regulated via transcription regulators Tup1p and Cyc8p, but in a divergent manner. Biofilm formation is regulated by Cyc8p and Tup1p antagonistically: Cyc8p functions as a repressor of FLO11 gene expression and biofilm formation, whereas Tup1p counteracts the Cyc8p repressor function and positively regulates biofilm formation and Flo11p expression. In addition, Tup1p stabilizes Flo11p probably by repressing a gene coding for a cell wall or extracellular protease that is involved in Flo11p degradation. In contrast, formation of BR-F flocs is co-repressed by the Cyc8p-Tup1p complex. These findings point to different mechanisms involved in yeast multicellularity.
Keywords: Nuclear Proteins; Repressor Proteins; Saccharomyces cerevisiae Proteins; jaderné proteiny; Flocculation; represorové proteiny; druhová specificita; Saccharomyces cerevisiae; Yeast multicellular structures; Species Specificity; Colony biofilm; Cyc8p and Tup1p; Adhesion and invasion; buněčná stěna; Gene Expression Regulation, Fungal; regulace genové exprese u hub; biofilmy; Saccharomyces cerevisiae - proteiny; Biofilms; Cell Wall